(untitled) (Mustansiria Dental Journal, 2018)
The present study evaluates crestal bone loss around dental implants (retrospectively and prospectively) and determines the prognosis of dental implant through bone level estimation. Bone level was measured around 354 implants in 88 patients retrospectively and 97 implants in 31 patients prospectively, digital panoramic radiograph were taken during recall appointments, and analysis with a computer software associated method to measure the actual bone loss in mesial and distal side of the implant during these periods. Over all, the studied implants, experienced most of its crestal bone loss during the preloading period, followed by dramatic decrease in bone loss rate through the subsequent study intervals. The result of the present study showed that there is significant positive correlation between crestal bone loss and age, female showed significantly higher amount of bone loss than male in stage-1, while the apposite figure found in stage-2. Data analysis during preloading time indicates significant bone loss with implant location, while highly significant bone loss had been detected with maxillary arch, fine trabecular bone density, immediate implant, complete edentulous cases, While implant length, implant diameter and implant stability had a non significant effects on crestal bone loss.